Система преобразования энергии, генерируемой в полосе отчуждения железной дороги с помощью солнечных панелей - Гончаров, Юрий Петрович; Сокол, Евгений Иванович; Замаруев, Владимир Васильевич; Ивахно, Владимир Викторович; Кривошеев, Сергей Юрьевич; Ересько, Александр Вячеславович; Маляренко, Евгений Анатольевич; Стысло, Богдан Александрович; Панасенко, Н. В.; Сыченко, В. Г.; Косарев, Е. Н. (Приазовський державний технічний університет, 2015)
Рассмотрена возможность размещения фотогенераторов в зоне отчуждения железной дороги. Предложена структурная и электрическая схемы системы распределенной генерации для питания электрической тяги постоянного тока. Произведен выбор и обоснование частоты промежуточных звеньев преобразователей, используемых в системе.

The arising deficiency of traditional energy sources necessitates the use of renewable energetics. One of the advantages of the sources of renewable energy is the possibility of constructing a system of distributed generation. For conditions of Ukraine distributed generators placed along the existing facilities with a linear arrangement are the most promising. The railways with their land dispossession belt can be used for these purposes. The distributed generation systems in railway transport can also be used in the regions with an unstable electricity supply, improving power quality, feeding autonomous objects of railway infrastructure. Distributed generation equipment can be used to reduce bias and voltage unbalance in power systems of stationary consumers. The projects using solar energy for the needs of railway transport show their high adaptability and efficiency. The article is devoted to the development of the DC power supply system. The railway contains additional longitudinal DC line with an operating voltage of about 1 kV and a system of semiconductor converters for connecting the longitudinal line and the main contact system through matching modules. Sequential positioning of the longitudinal line and the photo module is consistent with their properties as a current source that is proportional to the intensity of solar radiation. Semiconductor converters should be made using the same "a forward" topology, which simplifies the electrical circuit. Amorphous magnetic alloy is the most promising material for the existing isolation transformers in the system. Proper value of the operating frequency of the AC intermediaries is about 1 kHz. Traction power supply system with distributed PV generation, discussed in this article, will make it possible to put into practice the concept of intellectual traction power supply, optimizing the process of electric energy consumption in the traction network.
Transformation of power generated in railways dispossession belt by solar
Keywords: фотогенератор; трансформатор; сеть контактная; distributed system; photogenerator; converter; high-frequency transformer; contact line; roadway